Relações entre crenças de autoeficácia docente de licenciandos em Matemática, suas fontes e conhecimentos pedagógicos da prática docente no contexto do estágio supervisionado - Klein, Janete Aparecida (2023)
This study aims to analyze and understand the relationships between teaching self-efficacy beliefs of Mathematics undergraduate students, their sources and the pedagogical knowledge of teaching practice mobilized in the context of supervised internship. The theoretical framework integrates two themes: belief in self-efficacy, based on Social Cognitive Theory and; pedagogical knowledge, within Knowledge for Teaching. The study is exploratory and non-experimental, with a quantitative-qualitative methodological design for data production and analysis. A total of 104 academics from Mathematics Degree courses from six Brazilian public universities, enrolled in the supervised curricular internship, participated in the research. The data production instruments were: a characterization and perception questionnaire about initial training; construction of a teaching self-efficacy belief scale; scale of sources of teaching self-efficacy beliefs; reflective journals; internship reports. The data were produced in two stages: 1) elaboration, evaluation and validation of the Scale- 1- Scale of Beliefs of Teaching Self-efficacy of Undergraduates in Mathematics in Relation to Pedagogical Knowledge in the context of the Supervised Internship and the Scale- 2- Scale of Sources of Teaching Self-Efficacy Beliefs in Relation to Pedagogical Knowledge in the context of Supervised Internship; elaboration and application of the questionnaire Profile and Perceptions of Mathematics Graduates about their Initial Formation; 2) content analysis of reflective diaries and internship reports of six undergraduates. Results of the first stage: a) validation with high internal reliability of the two Scales, being Scale-1, with Cronbach's alpha at α=0.92 and Scale-2, with α=0.86; factorial validity showed internal consistency of the Scales; b) teaching self-efficacy beliefs and sources with high bias. At the beginning of the internship, undergraduates demonstrated high teaching self-efficacy beliefs in the dimensions Use of Information and Communication Technologies and Intentionality of Teaching Action. The most recurrent sources of self-efficacy were Vicarious Experience, followed by Social Persuasion. Teacher self-efficacy showed a relationship, among others, with different school mathematical experiences, in the choice of course, and also in pedagogical experiences in course subjects developed for Elementary and High School, among others. At the end of the internship, the content analysis revealed high self-efficacy of six undergraduates, especially in the dimensions of Lesson Planning and Teaching Action Intentionality. The most recurrent sources of self-efficacy were Direct Experience and Social Persuasion. Formative experiences with school mathematics, real teaching experiences, collaborative work, experience reports, and analysis and reflection on the teaching practice itself, during the internship, overlapped the vicarious experiences. Feedback from the advisor, supervisor, and colleagues fostered the graduates' positive self-efficacy. From this dissertation, it is considered necessary to develop training spaces for dialogue, as well as diversified pedagogical experiences involving different technologies, in addition to strengthening the praxis between theory and practice during training. It is observed the importance of developing a greater university-school interaction, which enables the integral formation of the teacher, which implies the development and strengthening of significant and positive teaching self-efficacy for future teachers. The Teaching Self-Efficacy Scale for Mathematics Graduates and Sources prove to be useful for other similar research and can be adapted to other areas or to be used with basic education teachers.